Optimization of Layer Thicknesses for Dual-Layer Bit-Patterned Media Recording (BPMR) Systems - Natthakan Rueangnetr; Chanon Warisarn; Simon John Greaves (IEEE Transactions on Magnetics, 2024)
To increase the areal density (AD) of magnetic recording, we have investigated the effect of the thicknesses of the individual layers in dual-layer bit-patterned media recording (BPMR) systems. The recording media consisted of two, discrete recording layers, separated by a non-magnetic spacer layer. The bottom, or lower, recording layer thickness and the head-medium spacing (HMS) were fixed, while the top, or upper, recording layer thickness was varied to adjust the spacing between the reader and the bottom layer. By varying the layer thicknesses, together with arranging the bit islands in a staggered, overlapping manner, the readback signal strengths from the upper and lower layers could be adjusted and balanced. To determine the bit-error-rate improvement needed to reach a target AD of 4.0 terabits per square inch (Tbits/in2), i.e., 2.0 Tbits/in2 per layer, the readback signal was processed using an iterative method. The results showed that the proposed design could outperform a single-layer (SL) BPMR system.
Keywords: Error Correcting Code Techniques; Advanced Wireless Communication Techniques; Video Coding and Compression Technologies